2014
DOI: 10.1515/iral-2014-0013
|View full text |Cite
|
Sign up to set email alerts
|

L2 learners' sensitivity to semantic and morphophonological information on Swahili nouns

Abstract: Previous research demonstrates that L2 learners are sensitive to morphophonological and semantic information regarding grammatical gender in European languages (e.g., Spinner & Juffs, 2008). In this study we examine the use of morphophonological and semantic information by two groups of Englishspeaking learners acquiring Swahili gender (noun class). The results of an oral agreement-marking task, a written gender assignment task, and interviews indicate that learners are sensitive to morphophonological informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
1
4
0
2
Order By: Relevance
“…Alarcón (2009Alarcón ( , 2010; see also Belacchi & Cubelli, 2012) further suggests that in pronoun resolution native speakers take equal advantage of morphological and semantic cues, while nonnative speakers favor semantic cues rather than morphological cues, with the latter being less available for automatic access. Indeed, animacy has been confirmed to have a privileged status for transfer to nonnative processing, which is accessible outside of the L1 linguistic system (semantic core hypothesis, Spinner & Thomas, 2014). If the gender biases in our data can only be observed with animate noun referents, it would confirm prior findings that the semantic gender component allows for an easier, more transparent mapping between biological gender and formal gender, leading to the misinterpretation of the grammatical gender as semantic.…”
Section: Present Studysupporting
confidence: 82%
See 1 more Smart Citation
“…Alarcón (2009Alarcón ( , 2010; see also Belacchi & Cubelli, 2012) further suggests that in pronoun resolution native speakers take equal advantage of morphological and semantic cues, while nonnative speakers favor semantic cues rather than morphological cues, with the latter being less available for automatic access. Indeed, animacy has been confirmed to have a privileged status for transfer to nonnative processing, which is accessible outside of the L1 linguistic system (semantic core hypothesis, Spinner & Thomas, 2014). If the gender biases in our data can only be observed with animate noun referents, it would confirm prior findings that the semantic gender component allows for an easier, more transparent mapping between biological gender and formal gender, leading to the misinterpretation of the grammatical gender as semantic.…”
Section: Present Studysupporting
confidence: 82%
“…Sagarra & Herschensohn, 2008), larger mismatch effects in sentences with violations (Deustch, Bentin & Katz, 1999), are more resistant to the attractions errors due to the adjacent location (Deutsch & Bentin 2001), and evoke fewer agreement production errors (Antón-Méndéz, 1999;Vigliocco & Franck, 1999). Advanced L2 speakers also show the same tendencies for the processing preference of the animate nouns (Alarcón, 2009(Alarcón, , 2010Spinner & Thomas, 2014). The superior status of animate nouns have been associated with the fact that the semantic component of gender in animate referents associated with biological gender reduces the processing demands for establishing agreement and coreference with other parts of the sentence (Deutsch et al, 1999).…”
Section: Present Studymentioning
confidence: 99%
“…In this instance, Rodríguez found that the English-speaking learners of Spanish were sensitive to morphological mismatches during a reading test. Similarly, Spinner and Thomas (2014) found that English-speaking learners of Swahili (elementary to intermediate L2 Swahili) attend to morphophonological features when determining grammatical gender, even though English itself does not typically mark for gender. Addressing a wider range of L1s, Wu (2016) also uncovered priming differences between advanced learners of English with different L1s ranging from morphologically-rich Turkish to morphologically-poor Chinese.…”
Section: Learner Language and Productivitymentioning
confidence: 93%
“…Taking the position that learners do not decompose complex word forms, Neubauer and Clahsen (2009) conclude from their research on advanced Polish-speaking learners of German, that L2 learners do not decompose inflected forms, instead relying on whole-word processing. However, while there is evidence that adults make less use of syntactic structures, most research refutes the strong claim that learners are not at all sensitive to L2 morphology (e.g., Bosch et al, 2017;Langman & Bayley, 2002;Rodríguez, 2013;Rehak & Juffs, 2010;Spinner & Thomas, 2014).…”
Section: Learner Language and Productivitymentioning
confidence: 95%
“…Juose klausiama, kuriais giminės požymiais -semantiniais ar morfologiniaisremiasi mokiniai tada, kai atpažįsta semantiškai motyvuotą daiktavardžio giminę, ar kai su juo derina kitas kalbos dalis (plg. Oliphant 1997; Dewaele, Véronique 2001;Franceschina 2005;Menzel 2005, Spinner, Thomas 2014, arba kurias giminės reikšmės (vyriškosios ar moteriškosios) formas mokiniai vartoja taisyklingiau (plg.…”
Section: įVadasunclassified